Isolation and purification of Keratinophilic and dermatophytic fungi from some public places of Jaipur city, India - Soniya Bairwa (International Journal of Pharma and Bio Sciences, 2020)
Soil is the main source for the growth and occurrence of keratinophilic fungi due to its richness in keratinous substrates. Keratinophilic fungi along with dermatophytes causes human and animal mycoses. In the present study eighty soil samples were collected from bus stands and railway stations in the vicinity of Jaipur city, Rajasthan, India and observed the prevalence of keratinophilic fungi. For this purpose, hair baiting technique was used. A total of 98 isolates belonging to seven genera were recovered. Chrysosporium tropicum (26.53%) was the most prevalent species followed by Chrysosporium indicum (12.24%), Microsporum gypseum (11.22%) and Trichophyton rubrum (8.16%), T. terrestre (7.14%), A. fumigates (6.12%) and Fusarium oxysporum (4.08%) etc. This study showed that soil of these places may be notable reservoirs of certain kreatinophilic and dermatophytic fungi and these places explored first time in Jaipur city, India.